Health Care Determinants of Child Survival in Pakistan (The Pakistan Development Review, 1994)
The health and survival status of children which are important indicators of social well-being, have become a subject of great concern in Pakistan in recent years. The available literature suggests that infant and child death rates in Pakistan are high even in the context of the Asian region and progress in health and survival of children has been much less than the desired level [World Bank (1993)]. Although estimates of infant and child mortality rates as derived from various data sources in Pakistan show great variation, 1 the available evidence indicates· that nearly 58 percent of all deaths occur among children under five years of age, 36 percent die during infancy and more than half of all infant deaths occur within the first four weeks of their birth [Irfan (1986); Afzal et al. (1988); Rukanuddin and Parooqui (1988); Sathar (1994)]. Recognising the fact that most of these deaths could be prevented, it is important to study the processes that are likely to influence the survival chances of children, the health care factors in particular, which are important components of mortality change.